2006
DOI: 10.1007/s00726-005-0293-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intake of caffeine during gestation down regulates metabotropic glutamate receptors in maternal and fetal rat heart

Abstract: Caffeine is the most widely consumed substance in the world which antagonizes adenosine effects. Adenosine acting through A(1) receptors inhibits glutamate release which binds to metabotropic glutamate receptors (mGluRs). Recently, we have shown that maternal caffeine intake during gestation causes down-regulation of A(1) and metabotropic glutamate receptors in the brain of both rat mothers and fetuses. In the present work we provide evidence that caffeine also affects receptors in hearts, causing a decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
1
17
0
1
Order By: Relevance
“…In the human heart, mGlu receptors 1 and 5 but not mGlu2/3 were found in atrial intramural ganglia, atrial and ventricular cardiocytes, and bundle of Hiss (Gill et al, 2007). In addition, the components of mGlu/PLC pathway have been studied in the pregnant rat heart (Iglesias et al, 2006). It is noteworthy that maternal intake of caffeine during rat gestation causes downregulation of mGlu1 protein level in the fetus heart and a loss of responsivity to several mGlu receptor agonists in membrane preparations isolated from the heart of the fetus (Iglesias et al, 2006).…”
Section: Other Tissues Expressing Metabotropic Glutamate Receptorsmentioning
confidence: 99%
“…In the human heart, mGlu receptors 1 and 5 but not mGlu2/3 were found in atrial intramural ganglia, atrial and ventricular cardiocytes, and bundle of Hiss (Gill et al, 2007). In addition, the components of mGlu/PLC pathway have been studied in the pregnant rat heart (Iglesias et al, 2006). It is noteworthy that maternal intake of caffeine during rat gestation causes downregulation of mGlu1 protein level in the fetus heart and a loss of responsivity to several mGlu receptor agonists in membrane preparations isolated from the heart of the fetus (Iglesias et al, 2006).…”
Section: Other Tissues Expressing Metabotropic Glutamate Receptorsmentioning
confidence: 99%
“…Adenosine is a nucleoside distributed in the heart and involved in cardiovascular response (Flood et al 2002, Xu et al 2005, Iglesias et al 2006). Hence, caffeine as a nonselective adenosine antagonist is expected to influence cardiovascular system.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Metabotropic glutamate receptors have been proved to be present in the heart and play a role in its physiology (Us et al 2001, Iglesias et al 2006. Recently, (Iglesias et al 2006) have demonstrated down-regulation of mGluRs and a decrease in Gq/11 and PLCβ proteins in fetal rat hearts exposed to caffeine via maternal intake.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
See 2 more Smart Citations